Free NADH Concentration Is Kept Constant in Plant Mitochondria under Different Metabolic Conditions - Kasimova, Marina R; Grigiene, Jurgita; Krab, Klaas; Hagedorn, Peter H; Flyvbjerg, Henrik; Andersen, Peter E; Møller, Ian M (The Plant cell, 2006)
The reduced coenzyme NADH plays a central role in mitochondrial respiratory metabolism. However, reports on the amount of free NADH in mitochondria are sparse and contradictory. We first determined the emission spectrum of NADH bound to proteins using isothermal titration calorimetry combined with fluorescence spectroscopy. The NADH content of actively respiring mitochondria (from potato tubers [Solanum tuberosum cv Bintje]) in different metabolic states was then measured by spectral decomposition analysis of fluorescence emission spectra. Most of the mitochondrial NADH is bound to proteins, and the amount is low in state 3 (substrate + ADP present) and high in state 2 (only substrate present) and state 4 (substrate + ATP). By contrast, the amount of free NADH is low but relatively constant, even increasing a little in state 3. Using modeling, we show that these results can be explained by a 2.5- to 3-fold weaker average binding of NADH to mitochondrial protein in state 3 compared with state 4. This indicates that there is a specific mechanism for free NADH homeostasis and that the concentration of free NADH in the mitochondrial matrix per se does not play a regulatory role in mitochondrial metabolism. These findings have far-reaching consequences for the interpretation of cellular metabolism.